What is the best way to improve your swimming? - Hull, M. (1999)
About the question: What is the best way to improve your swimming? Plan A. Swim hard doing your normal swimming movements. Plan B. Spend 20% of your workout time stretching so you can improve the anatomical efficiency of your swimming movements and then swim hard for the other 80% of the time you have available. HINT: Plan 'B' works better.